From Disease Burden to Workforce Policy: A Burden-Informed Framework for Health Workforce Planning in Indonesia. - Sri Wahyuni; Sahat Aditua Fandhitya Silalahi; Bondan Haryono; Ius Olianto; Oos Fatimah Rosyati (National Research and Innovation Agency, Indonesia, 2026)
Abstract:Stroke is the leading cause of death and disability in Indonesia, responsible for 18% of all deaths and 10.8% of total Disability-Adjusted Life Years (DALYs) in 2023, requiring sub-national and needs-based health workforce planning, rather than traditional methods relying on population density for its distribution. This study introduces a novel, burden-based workforce forecasting framework, a policy innovation designed to align health workforce supply with actual epidemiological needs. A descriptive analysis combined Global Burden of Disease (GBD) 2023 estimates for stroke with national health workforce registries to identify critical mismatches in specialist distribution. The results reveal that high burden provinces such as East Kalimantan and North Sulawesi face significant shortages of neurologists, while lower burden regions like Bali show disproportionate number of specialists. Beyond clinical gaps, the analysis highlights a failure in strategic technology management, many districts possess diagnostic hardware but lack the specialized human capital to operate them. This studyproposes a systemic transition toward precision policy by embedding predictive analytics and digital health innovations, such as teleradiology and AI-driven clinical decision support, into national development planning. By moving from traditional ratio-based methods, this framework offers a more equitable and cost-effective foundation for policy reform. The Indonesian case offers transferable lessons for other countries facing similar demographic and epidemiological transitions, a scalable template for low-middle income countries to optimize health system resilience and equity through evidence-based policy management.Keywords: stroke, GBD, disease burden, health workforce planning, technology policy management, Indonesia.